Early Coagulopathy is Associated With Increased Incidence of Ventilator-Associated Events Among Burn Patients. Issue 1 (January 2017) - Younan, Duraid; Griffin, Russell; Thompson, Maxwell; Swain, Thomas; Honkanen, Matthew; Crosby, James C.; Ellis, Chandra V.; Pittet, Jean-Francois; Kerby, Jeffrey D.
ABSTRACT: Objective: Coagulopathy is known to be associated with burn injury. Our group has shown that, in spinal cord injury patients, coagulopathy is associated with an increase in ventilator-associated pneumonia (VAP). We hypothesized that the same association exists between coagulopathic burn patients and ventilator-associated events. Methods: Patients admitted for burn care between January 1, 2011 and December 31, 2015 who required mechanical ventilation were included in the study. Ventilator-associated events (VAEs) as defined by the Center for Disease Control were categorized as no event, ventilator-associated condition, infection-related ventilator-associated complication, and possible VAP. Demographic, injury characteristics were compared among four international normalized ratio (INR) categories using analysis of variance and chi-square tests. Results: Four hundred four patients were admitted for burn care, of whom 263 met the inclusion criteria. One hundred eleven had normal INR, 59 had a slightly elevated INR (1.2–1.4), 33 had a moderately elevated INR (1.4–1.6), and 60 had a severely elevated INR (>1.6). Those with moderately and severely elevated INR were ventilated for a longer period ( P = 0.0034), had more days in the ICU ( P = 0.0010), and had longer hospital stay ( P = 0.0016). After adjusting for inhalation injury and total body surface area, patients with severely elevated INR were over four times as likely to have any VAE (OR: 4.16, 95% CI: 1.33–13.05) and 4.5 times as likely to develop infection-related ventilator-associated complication or possible ventilator-associated pneumonia combined (OR: 4.59, 1.35–15.67). Conclusions: Early coagulopathy is associated with a significantly increased incidence of VAEs in burn patients. While additional studies need to be conducted to verify these findings, early recognition and treatment could decrease VAEs.